Introduction to the humanities - Sanchez, Custodiosa A.; Abad, Paz F.;Jao, Loreto V. (Manila, Philippines : Rex Book Store, 2011)
Introduction to the Humanities introduces the students to the different areas of the arts giving them knowledge of the various subject areas it covers. Discussions and illustration of the Philippine arts and foreign arts are provided so the readers can fully understand their relevance to an individual and the society. This book will serve not only as a practical classroom textbook in the Humanities but also as a helpful reference book for the students in arts appreciation and related courses.
Preface -- Preface to the Revised Edition -- Introduction -- Part I. General Overview of Humanities -- Part II. Painting, Sculpture, and Architecture -- Part III. Literature and the Drama -- Part IV. Music and Dance -- Bibliography -- Appendix -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: HUMANITIES -- STUDY AND TEACHING